Genetics of anthracnose panel canker disease resistance and its relationship with yield and growth characters in half-sib progenies of rubber tree (Hevea brasiliensis) - Goncalves, PDS; Furtado, E. L.; Bataglia, O. C.; Ortolani, A. A.; May, A.; Belletti, G. O. (Soc Brasil Genetica, 1999)
Rubber tree [Hevea brasiliensis (Willd, ex Adr, de Juss.) Muell-Arg] anthracnose panel canker disease resistance, caused by Colletotrichum gloeosporioides (Penz.) Sacc., and growth and yield characters were assessed at three years old in the nursery, in 18 half-sib progenies. There were highly significant (P < 0.01) genetic differences among progenies for most characters. The genetic component of variance accounted for 3.37, 6.07, 12.74, 12.13, 19.82 and 3.58% of the phenotypic variance for anthracnose-infected area, anthracnose lesion stripe length, yield, girth, virgin bark thickness and total number of latex Vessel rings, respectively. Narrow-sense heritability estimates for the above characters were 13.45, 24.30, 50.97, 48.52, 79.30 and 14.30%, respectively. No significant genetic correlations were found among anthracnose panel canker resistance, yield and growth characters. The frequency distribution of anthracnose-infected area and anthracnose lesion stripe length suggests polygenic control. Selecting the best three progenies out of 18 progenies would result in a genetic gain of 12.87 and 24.24% for infected area and lesion stripe length, respectively. The best five selected individuals out of 50 individuals within each progeny would result in a genetic gain of 9.47 and 24.62%, with a total gain of 22.34 and 48.87% for these two characters, respectively.